Clinical Trial Design for HIV Prevention Research: Determining Standards of Prevention. (17th September 2014) - Dawson, Liza; Zwerski, Sheryl
Abstract This article seeks to advance ethical dialogue on choosing standards of prevention in clinical trials testing improved biomedical prevention methods for HIV. The stakes in this area of research are high, given the continued high rates of infection in many countries and the budget limitations that have constrained efforts to expand treatment for all who are currently HIV‐infected. New prevention methods are still needed; at the same time, some existing prevention and treatment interventions have been proven effective but are not yet widely available in the countries where they most urgently needed. The ethical tensions in this field of clinical research are well known and have been the subject of extensive debate. There is no single clinical trial design that can optimize all the ethically important goals and commitments involved in research. Several recent articles have described the current ethical difficulties in designing HIV prevention trials, especially in resource limited settings; however, there is no consensus on how to handle clinical trial design decisions, and existing international ethical guidelines offer conflicting advice. This article acknowledges these deep ethical dilemmas and moves beyond a simple descriptive approach to advance an organized method for considering what clinical trial designs will be ethically acceptable for HIV prevention trials, balancing the relevant criteria and providing justification for specific design decisions.